2000
DOI: 10.1136/jnnp.68.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Urinary dysfunction and orthostatic hypotension in multiple system atrophy: which is the more common and earlier manifestation?

Abstract: Objectives-Urinary dysfunction and orthostatic hypotension are the prominent autonomic features in multiple system atrophy (MSA). A detailed questionnaire was given and autonomic function tests were performed in 121 patients with MSA concerning both urinary and cardiovascular systems. Methods-Replies to the questionnaire on autonomic symptoms were obtained from 121 patients including three clinical variants; olivopontocerebellar atrophy (OPCA) type in 48, striatonigral degeneration (SND) type in 17, and Shy-Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 25 publications
8
94
0
2
Order By: Relevance
“…Approximately 50% of patients are initially misdiagnosed as having PD [Quinn, 1995] and since urinary symptoms occur so early [Beck et al, 1994;Sakakibara et al, 2000] the commonest presentation to a Urologist will be of a patient of either gender (mean age 52 years) usually complaining of urinary urgency and urgency incontinence [Beck et al, 1994] or much less commonly, urinary retention. The patient may at this stage have subtle symptoms of other neurological involvements with a somewhat expressionless face, impaired movements and an early akinetic rigid syndrome, or a cerebellar syndrome with unsteadiness and dysarthria.…”
Section: Differential Diagnosis Of Pd In Patients With Urinary Incontmentioning
confidence: 99%
“…Approximately 50% of patients are initially misdiagnosed as having PD [Quinn, 1995] and since urinary symptoms occur so early [Beck et al, 1994;Sakakibara et al, 2000] the commonest presentation to a Urologist will be of a patient of either gender (mean age 52 years) usually complaining of urinary urgency and urgency incontinence [Beck et al, 1994] or much less commonly, urinary retention. The patient may at this stage have subtle symptoms of other neurological involvements with a somewhat expressionless face, impaired movements and an early akinetic rigid syndrome, or a cerebellar syndrome with unsteadiness and dysarthria.…”
Section: Differential Diagnosis Of Pd In Patients With Urinary Incontmentioning
confidence: 99%
“…It is well documented that MSA-C patients (MSA of the cerebellar type) and MSA-P patients show differences in both the severity and onset of OH 9 and it is noteworthy that several studies combined these patients in their analyses. 7,8 It has also been demonstrated that BRS is lower in Parkinson's disease patients with orthostatic hypotension (PDOH) than in those without OH 5,10 and that a lower BRS is correlated with a higher score on the Hoehn and Yahr scale of severity.…”
Section: Jcnmentioning
confidence: 99%
“…Urinary dysfunction appears to be more common and is often an earlier manifestation than are the symptoms of OH in MSA, 22 but the chronological relationship between the onset of development of ED and orthostatic hypotensive symptoms has not previously been examined. This study presents a retrospective analysis of symptoms and results of relevant laboratory investigations in patients subsequently diagnosed as having MSA.…”
Section: Introductionmentioning
confidence: 99%